Institut zadržanja objave predpisa - Štrus, Dušan (Pravni letopis, 2025)
The institute suspending the publication of a regulation is an important, independent stage in the legislative process that occurs after the regulation has been adopted but before its promulgation, publication, and entry into force. It is a constitutional-law institute representing the period between the adoption of a regulation and its promulgation and publication, temporarily preventing its execution. Compared to other phases of the broader legislative process, this institute is less well known and often overlooked, which causes difficulties, particularly within the functioning of self-governing local communities. The Constitution does not directly regulate this institute; rather, it arises as a legal consequence of certain constitutional- law mechanisms that may affect the final formation of a regulation after its adoption (e.g. a suspensive veto or a referendum). Legislation generally does not explicitly regulate this institute either, except in certain areas of local self-government. The suspension may occur ex lege, as a result of the expiry of a constitutionally or legally determined period, or due to a specific legally relevant event, such as the filing of a suspensive veto or a request for a referendum. Failure to observe this institute may have a serious legal consequence in constitutional court proceedings—namely, that the regulation is deemed not to have come into existence at all.
Keywords: Constitutional Court; Državni zbor; National Assembly; objava; predpis; promulgation; publication; razglasitev; referendum; regulation; samoupravna lokalna skupnost; self-governing local community; suspension; suspensive veto; suspenzivni veto; Ustavno sodišče; vacatio legis; zadržanje